Bmo-miR-2758 Targets BmFMBP-1 (Lepidoptera: Bombycidae) and Suppresses Its Expression in BmN Cells. Issue 1 (21st March 2016) - Wang, Xin; Tang, Shunming; Song, Fei; Chen, Chen; Guo, Xijie; Shen, Xingjia
Abstract: MicroRNAs (miRNAs) are an abundant family of endogenous noncoding small RNA molecules. They play crucial roles on regulation of life processes both in plants and animals. Fibroin modulator binding protein-1 (FMBP-1) is a silk gland transcription factor of Bombyx mori, which is considered as a trans-activator of fibroin genes. And bioinformatics prediction showed that at the 3′ untranslated region (3′ UTR) of BmFMBP- 1 there were binding sites for three bmo-miRNAs, bmo-miR-2b*, bmo-miR-305, and bmo-miR-2758, separately. In order to validate whether these bmo-miRNAs involved in the regulation of BmFMBP -1 expression, the expression levels of three bmo-miRNAs and BmFMBP -1 in the middle silk gland (MSG) and posterior silk gland (PSG) during the fourth- and fifth-larval stages of B. mori were measured by semi-quantitative reverse transcription polymerase chain reaction. The results revealed that the expression level of bmo-miR-2758 was the highest in the three, and it expressed higher in the PSG than in the MSG with a similar expression pattern as BmFMBP- 1, implying that bmo-miR-2758 may involved in regulation of BmFMBP -1. To validate the regulation function of bmo-miR-2758 on BmFMBP- 1, recombinant plasmids pcDNA3 [ ie 1- egfp -pri-bmo-miR-2758-SV40] and pGL3 [ A 3- luc-FMBP- 1 3′ UTR-SV40] were constructed and co-transfected in BmN cells. The dual-luciferase reporter assay system was used for assay of transient expression. The results showed that the expression of the luciferase reporter was significantly decreased when pGL3 [ A 3- luc-FMBP- 1 3′ UTR-SV40] co-transfected with pcDNA3 [ ie 1- egfp -pri-bmo-miR-2758-SV40] ( P  < 0.01). Furthermore, when the artificial antisense RNA of bmo-miR-2758 (inhibitor) was added to the above co-transfection, the expression of the luciferase reporter was recovered significantly ( P  < 0.01). These results suggest that bmo-miR-2758 represses the expression of BmFMBP -1 in vitro.